Caracteristica fisico-quimicas del bocachico (Ichthyoelephas humeralis). - Leon Cedeño, Dario Gonzalo (2016)
This research was performed in the laboratory of the Faculty of Animal Sciences at the University of Quevedo and whose objective was to analyze the physico-chemical characteristics of bocachico (Prochilodus magdalenae), after the cleaning process, the bocachicos, were transported where they were stored in a frozen state (-18 ° C) for the duration of the investigation, the laboratory is located in the province of Los Ríos in the Canton Quevedo under geographic coordinates 780 32 '9.7' 'altitude west, S OO0 14 '997' 'south altitude. The investigation lasted four months. The results obtained from the research project were: Bocachico had a yield of 47.11% fillets, skin over bone the 23.14%, 14.63% the viscera and head 15.2% compared to weighing the fish. Bocachico muscle obtained a moisture content of 77.76%, 19.73% protein, 1.59% ash and 2.47% fat. Bocachico meat presented a drip loss of 4.29% and 24.72% .and cooked the pH 6.63. Meat bocachico presented a value L 62 which tends to be a lot more white meat, whereas when the red is analyzed (a +) records a value of 16.33 and analyzing the yellowness (b +), gives a value of 7.54. Keywords. Bocachico, physical composition, chemistry,